Examining Success and Sustainability of Academic Writing: A Case Study of Two Writing-Group Models - Olszewska, Kinga; Lock, Jennifer (Canadian Journal of Higher Education, 2017)
In contemporary higher education there is a growing demand for academics to increase their publication output. This requirement raises the question of how institutions can best support a sustainable academic writing culture, which is needed to challenge the assumption that all academics know how to write for publication. This case study examines two models used in a Faculty of Education to support writing groups for academic staff. From the analysis of reflective journals, interviews, and field notes, we identified four factors that influence the success of writing groups, as well as six conditions that support the development of sustainable academic writing. We have learned from the study that the success of a writing group is predicated on a collaborative practice that blends relational, communal, and institutional forms of sustainability in a purposeful, engaged, and reflexive way.